(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The issue of human trafficking in India is the primary subject of this investigation. According toall of the research, the major reasons why people become victims of human trafficking continue to beneglected in favour of illegal immigration or prostitution. Academics and politicians have, for the mostpart, turned a blind eye to structural inequities, practices that are culturally sanctioned, poverty,economic instability, forced labour, and gender-based violence. The victims of human trafficking in Indiahave a higher priority than the factors that contribute to and facilitate the problem. This results in theprovision of preventative measures. Human smuggling has existed since the beginning of time. It has adetrimental impact on the nation as a whole, both in terms of its physical health and its mental state.Their domain is one of complete and utter stagnation. The whole situation makes me feel ashamed andhumiliated. It’s a rather significant issue from a legal standpoint. An investigation conducted by theUnited States government estimates that there are 27 million victims around the globe. Protect their mostfundamental human rights, encourage their progress, and keep them secure from the problems faced bythe rest of the world. In spite of the fact that there are several laws and government programmesdesigned to make their life easier, there are still many barriers. It is essential to raise awareness ofhuman trafficking in our nation because it is a significant problem that has to be addressed as soon aspossible in order to ensure that all victims are heard and that they get the assistance they need toflourish. As a direct consequence of this, victims of human trafficking in India face a wide range ofmental and legal obstacles, in addition to the possibility of becoming victims of trafficking a secondtime. According to the findings of the study, increasing the number of victim-centered interventions willassist with forthcoming new traffic cases. As a direct result of this, they look at the current condition ofthe laws regarding human trafficking in the United States, as well as the challenges and obstacles thatare experienced by those who have been victims of human trafficking.